PLURALISME PENYELENGGARAAN PENDIDIKAN BERBASIS KEAGAMAAN KRISTEN DAN KATOLIK DI KABUPATEN BANGKALAN - Wardhana, Indra Jaya Kusuma; Prastiwi, Merlia Indah; Suseno, Klaudius Febrianto Ari (Universitas Muria Kudus, 2024)
This research aims to take a space that has not received attention in the field of education that intersects with the complexity of community elements towards religious minority groups. Therefore, it is important to tackle the conception of pluralism in the implementation of non-Muslim religious-based education as a representation of the diversity of multicultural values of Madura. This research uses a qualitative methodology with an ethnomethodological approach. This study focuses on the assumption of